2016
DOI: 10.1111/mmi.13568
|View full text |Cite
|
Sign up to set email alerts
|

Maf1 is a negative regulator of transcription in Trypanosoma brucei

Abstract: RNA polymerase III (Pol III) produces small RNA molecules that play essential roles in mRNA processing and translation. Maf1, originally described as a negative regulator of Pol III transcription, has been studied from yeast to human. Here we characterized Maf1 in the parasitic protozoa Trypanosoma brucei (TbMaf1), representing the first report to analyse Maf1 in an early-diverged eukaryote. While Maf1 is generally encoded by a single-copy gene, the T. brucei genome contains two almost identical TbMaf1 genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
(177 reference statements)
0
11
0
Order By: Relevance
“…The ChIP procedures were performed as previously described [31]. Briefly, 2 × 10 8 promastigotes were cross-linked with formaldehyde (final concentration of 1%) for 5 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ChIP procedures were performed as previously described [31]. Briefly, 2 × 10 8 promastigotes were cross-linked with formaldehyde (final concentration of 1%) for 5 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, knockdown analysis by RNA interference demonstrated that Brf1 is indeed involved in Pol III transcription and that it is indispensable for cell survival of procyclic forms of T. brucei [30]. Another protein that participates in the regulation of Pol III transcription in T. brucei is Maf1, which inhibits tRNA and snRNA transcription by associating with their promoter regions [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, several reports implicated various proteins in RNA Pol I and Pol III transcription regulation (Romero‐Meza et al. ; Stanne et al. ), while little is known about the factors involved in transcriptional regulation of Pol II‐driven genes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been recently shown that TbMAF1, a negative regulator of RNA Pol III transcription, also downregulates transcription of SL‐RNA genes (Romero‐Meza et al. ). Thus, it seems that multiple negative regulators participate in the transcriptional control of this important molecule in trypanosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ablation of subunit Brf1 of TFIIIB in T. brucei reduced the expression of all Pol III-dependent genes analyzed, including 5S rRNA genes [102]. Interestingly, contrary to what occurs in other organisms, the downregulation or overexpression of the negative regulator Maf1 did not significantly change the levels of 5S rRNA in T. brucei [103].…”
Section: Ribosomal Rna Genesmentioning
confidence: 99%